Digital Payment Systems and Their Role in Shaping a Cashless Society - Yona Fitri; Muhammad Irwan Padli Nasution; Muhammad Habibi Siregar (LPPM ISNJ Bengkalis, 2026)
Purpose – This study aims to analyze the role of digital payment systems in shaping a cashless society among university students, focusing on their experiences and perceptions in using digital payment platforms such as e-wallets, mobile banking, and QR-based payments. Method – The research employs a qualitative approach using a phenomenological method. Data were collected through in-depth interviews with selected informants using purposive sampling and analyzed using thematic analysis, including coding, categorization, and theme development. Findings – The findings reveal that digital payment systems have become an essential part of students’ daily financial activities, significantly reducing reliance on cash transactions. The adoption is influenced by perceived ease of use, perceived usefulness, trust, and social influence, with social influence emerging as the most dominant factor. The study also identifies both positive and negative behavioral impacts, including increased efficiency as well as impulsive spending tendencies, and notes that from an Islamic economic perspective, digital payment systems are considered permissible as long as they comply with Sharia principles. Implications – Theoretically, the study contributes to understanding the behavioral and religious dimensions of digital payment adoption among students. Practically, it implies that strengthening digital infrastructure, enhancing financial literacy, and ensuring Sharia compliance are crucial for supporting sustainable and inclusive cashless society development.